METHODOLOGY OF TECHNIQUE PREPARATION FOR LOW VISION JAVELIN THROWERS - Milan Matić; Srđan Jovović (Sport Mont, 2013)
Javelin throwing discipline for disabled people has been expanding couple of years back. In addition, world’s records have been improving year after year. The esential part in preparation of low vision javelin throwers is mastering the technique elements, crucial for acquiring better results. Method of theoretical analysis, decriptive and comparative methods of survey were applied. Relevant knowledge in the area of low vision javelin throwers was analyzed and systematized, and then interpretated theoretically and applied on the top javelin thrower, which served as a base for the inovative apporoach in methodology and praxis with disabled people. Due to visual impairment, the coordination and balance are challenged. This limitation practically makes the difference in methodology, explained in this article. Apart from the goals focused on improving the condition and results on competitions, more specialized goals should be considered, e.g. improving of orientation, balance and socialization process for the people who have low vision. Special approach used in the technique preparation brought the significant improvement in techique of our famous Paralympian Grlica Miloš. In addition to the technique improvement he acquired better results on the big competitions and a few worldwide valuable prizes were won. The area of ’sport for disabled people’ is not enough present in the praxis of sport’s workers. More articles and scientific surveys on this topic are needed for further work and results improvement with these kind of sportsmen.